KINERJA PEREKONOMIAN INDONESIA DENGAN KENAIKAN HARGA MINYAK MENTAH DUNIA - A. Elly Samah; Yati Nuryati (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2008)
World market prices of crude oil have three digits, which has reached US 105,07 per barrel in September 2008. Rising oil prices are affecting the economy in the world including Indonesia, because the oil not only determined by supply and demand but also influenced by political factors. In Indonesia, rising prices had a significant impact to increased APBN deficits in 2008 amounted to Rp 14.4 triliyun. In 2007, Indonesia's economic growth reached 6.3%, the inflation rate reached 6.5% and according to estimates quarter I-2008 inflation rate would be high due to the world price of crude oil is still high. This is possible because the increasing of crude oil price will trigger the price rising of oil for domestic industry. The results showed that any increase in the oil price from 10 industries potentially also increase inflation of about 0.2-0.3 which was achieved in 2-3 months later. LPEM UI research indicates that any increase in the price of oil by 16.7 will make inflation rate amounted to 0.98. Inflation rate was mainly triggered by a rate increase and sea transportation of 2.8-4.2 and then overtaken by increasing construction costs amounting to 2,04 as the impact of the oil price increment. Based on the results of the analysis of the rise in world oil prices in the long term can interfere with Indonesia's economic growth. This is because in the long term increasing of crude oil price is likely to oil price and there is a tendency to rises subsidies. The implications of this are rising of oil price to APBN because of the Government has to increase subsidies for oil in order to anticipate increasing of crude oil prices in the. This subsidies are automatically burden APBN regarding of increasing of subsidies.